Geostrategic solutions to oil vulnerabilities in the Gulf region - Shikārah, Aḥmad ʻAbd al-Razzāq (Emirates lecture series, 2013)
"This paper intends to explore new models of global governance in producer-consumer relations to ameliorate the adverse effects of oil vulnerabilities such as supply disruptions or 'peak oil' scenarios. The paper will also seek to answer some vital questions regarding energy security, encompassing oil resource availability, reliability, affordability, and sustainability. In particular, it seeks to address the following questions, issues and concerns: Is there a clear strategic vision for overcoming oil vulnerabilities in the Arab Gulf? And if not, is there a need for one? How might major oil vulnerabilities involving transportation 'choke points' and critical infra-structure be overcome (i.e. operational mechanisms)? To what extent do current geo-political strategies or alternative energy options represent realistic propositions? This requires a cost-benefit analysis: if fossil fuel sources are affordable, will there be viable long-term opportunities to achieve the energy diversification called for in strategic planning? What innovative strategies may be employed to overcome oil vulnerabilities in the region?"--Introduction.